Embodied Indigenous knowledges protecting and privileging Indigenous peoples' ways of knowing, being and doing in undergraduate nursing education. Issue 2 (December 2020) - Drummond, Ali
Abstract: In the era of Indigenising the academy, health disciplines like nursing are required to teach Indigenous peoples' health, history and culture in their undergraduate programmes in order to meet national accreditation standards. This inclusion of Indigenous peoples' perspectives within nursing education towards registration thus qualifies respective Indigenous perspectives as legitimate parts of the Australian nursing profession's scope of practice, which may sound like a reason to celebrate. However, caution should be exercised. Indigenous and Western knowledge systems are incommensurable. The practice of defining Indigenous perspectives for placements within curricula could be likened to extractive colonialism. Thus, the commodifying of Indigenous perspectives in creating competitive education products is problematic. As a Meriam and Wuthathi man who grew up in the Zenadth Kes (Torres Straits) now living and working on Turrbul and Yuggera country, and as a nurse academic, being immersed in this space of contentions is my reality. In order to enhance the education preparation of nursing students I teach, while simultaneously protect my embodied Indigenous knowledges and the Indigenous perspectives included in the curricula I teach, I privilege Indigenous ways of knowing, being and doing in my teaching practice. This yarn is about my experience in this cultural interface.